Evolution of altruistic cooperation among nascent multicellular organisms. (15th April 2019) - Gulli, Jordan G.; Herron, Matthew D.; Ratcliff, William C.
Abstract: Cooperation is a classic solution to hostile environments that limit individual survival. In extreme cases this may lead to the evolution of new types of biological individuals (e.g., eusocial super‐organisms). We examined the potential for interindividual cooperation to evolve via experimental evolution, challenging nascent multicellular "snowflake yeast" with an environment in which solitary multicellular clusters experienced low survival. In response, snowflake yeast evolved to form cooperative groups composed of thousands of multicellular clusters that typically survive selection. Group formation occurred through the creation of protein aggregates, only arising in strains with high (>2%) rates of cell death. Nonetheless, it was adaptive and repeatable, although ultimately evolutionarily unstable. Extracellular protein aggregates act as a common good, as they can be exploited by cheats that do not contribute to aggregate production. These results highlight the importance of group formation as a mechanism for surviving environmental stress, and underscore the remarkable ease with which even simple multicellular entities may evolve—and lose—novel social traits.